Agatha Christie Marple. Series 2 [videorecording (DVD)] - Scherrer, Dominik, 1967-; Christie, Agatha, 1890-1976 (Miss Marple mysteries, 2006)
Miss Marple returns to help solve mysteries with her keen powers of observation and her quiet common-sense analysis. Sleeping murder: Gwenda arrives in England, looking forward to her impending marriage and new life in a lovely old coastal estate. But she begins to experience visions and Miss Marple concludes that the bride-to-be witnessed a murder in that very house as a child. By the pricking of my thumbs: Miss Marple teams up with two detectives, Tommy and Tuppence, to investigate the suspicious death of Tommy's Aunt Ada and sudden disappearance of Ada's friend, Mrs. Lancaster. The moving finger: When Jerry Burton moves to Lymstock to convalesce after a motorcycle crash, he meets villagers who traffic in gossip and double-entendres. But the accusations in several anonymous poison-pen letters go beyond the usual prattle and result in two citizens to commit suicide. Or were they murdered? The Sittaford Mystery: Among the guests at a Dartmoor hotel, a séance starts out as an amusing diversion to apss the time on a snowy evening but then takes a sinister turn.